2009
DOI: 10.1186/1756-9966-28-12
|View full text |Cite
|
Sign up to set email alerts
|

The biological effect of 125I seed continuous low dose rate irradiation in CL187 cells

Abstract: Background: To investigate the effectiveness and mechanism of 125 I seed continuous low-doserate irradiation on colonic cell line CL187 in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
42
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 38 publications
11
42
1
Order By: Relevance
“…Several studies have indicated that 125 I seed irradiation is effective in inducing cell apoptosis in pancreatic and colonic cancer cells (4,11,32 Previous studies have revealed that altered DNA methylation patterns may be critical in tumor inhibition resulting from consecutive low-energy 125 I irradiation (11). Ma et al (11) demonstrated that low-dose (4 Gy) 125 I irradiation causes a significant decrease in DNMT expression in pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated that 125 I seed irradiation is effective in inducing cell apoptosis in pancreatic and colonic cancer cells (4,11,32 Previous studies have revealed that altered DNA methylation patterns may be critical in tumor inhibition resulting from consecutive low-energy 125 I irradiation (11). Ma et al (11) demonstrated that low-dose (4 Gy) 125 I irradiation causes a significant decrease in DNMT expression in pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Iodine-125 ( 125 I) seeds have a long half-life and low energy with excellent stability, which has resulted in their extensive clinical use (4). Brachytherapy with low-dose 125 I seeds has been demonstrated to be an effective salvage therapy for gastric cancer and other malignant carcinomas (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…However, this remains controversial 18,23 and, moreover, this was reported in only one histological type of gastric cancer or cancer of other organs [24][25][26][27] Undifferentiated cancer cells are generally more sensitive to radiation. Thus, radiation effects may vary with cancer histology.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, I-125 seed implantation providing continuous low-dose-rate irradiation has been widely used to treat prostate cancer and other kinds of tumors in several Asian countries because of little trauma, strong effect, and fewer complications, [18][19][20][21] The efficacy of conventional radiation therapy for gastric cancer is controversial. In this study, we evaluated the in vitro and in vivo effects of continuous low-dose-rate irradiation by I-125 seeds on different histological types of gastric cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis after G2/M cell cycle arrest is either the main or a very important mechanism of the cell-killing effects of irradiation (21)(22)(23). Newly established radioresistant H460R cells showed decreased G2/M arrest in response to irradiation compared with parental H460R cells (Fig.…”
Section: Discussionmentioning
confidence: 99%